Information Retrieval on Exam Questions Referring to the Learning Plan Document Using Vector Space Model - Amalia Beladinna Arifa; Gita Fadila Fitriana; Ananda Rifkiy Hasan (Ikatan Ahli Informatika Indonesia (IAII), 2021)
One way to find out the quality of exam questions is by looking at the rules for writing exam questions made based on the subject or discussion contained in the learning plan document. Therefore, the exam questions that are arranged must be adjusted to the main material in each subject learning achievement. This study discusses the implementation of the concept in information retrieval systems using the Vector Space Model method. The Vector Space Model method has an advantage in query matching because it is able to match only part of the query with existing documents. In addition, the Vector Space Model method is also easy to adapt by adjusting parameters, including weighting parameters. The weighting calculation for each term that appears in the document uses TF-IDF. The purpose of this study is to design an information retrieval system to find the suitability of the exam question query with the subject contained in the learning plan document. The suitability is sorted based on the similarity value of the calculation results, from the largest value to the smallest value in the form of a percentage.